EUCAST disc diffusion criteria for the detection of mecA-Mediated β-lactam resistance in Staphylococcus pseudintermedius: oxacillin versus cefoxitin. (January 2020) - Skov, R.; Varga, A.; Matuschek, E.; Åhman, J.; Bemis, D.; Bengtsson, B.; Sunde, M.; Humphries, R.; Westblade, L.; Guardabassi, L.; Kahlmeter, G.
Abstract: Objectives: Until recently, the European Committee on Antimicrobial Susceptibility Testing (EUCAST) recommended the cefoxitin disc to screen for mecA -mediated β-lactam resistance in Staphylococcus pseudintermedius. A recent study indicated that cefoxitin was inferior to oxacillin in this respect. We have re-evaluated cefoxitin and oxacillin discs for screening for methicillin resistance in S. pseudintermedius. Methods: We included 224 animal and human S. pseudintermedius isolates from Europe ( n  = 108) and North America ( n  = 116), of which 109 were mecA -positive. Disc diffusion was performed per EUCAST recommendations using 30-μg cefoxitin and 1-μg oxacillin discs from three manufacturers and Mueller–Hinton agar from two manufacturers. Results: Cefoxitin inhibition zones ranged from 6 to 33 mm for mecA -positive S. pseudintermedius (MRSP) and from 29 to 41 mm for mecA -negative S. pseudintermedius (MSSP). The corresponding oxacillin zone intervals were 6–20 mm and 19–30 mm. For cefoxitin 16% (95% CI 14.8–18.0%) of the isolates were in the area where positive and negative results overlapped. For oxacillin the corresponding number was 2% (1.6–2.9%). For oxacillin a breakpoint of susceptible (S) ≥ 20 mm and resistant (R) <20 mm resulted in only 0.4% and 1.1% very major error and major error rates respectively. Conclusions: This investigation confirms that the 1-μg oxacillin disc predicts mecA- mediated methicillin resistance in S. pseudintermedius better than the 30-μg cefoxitin disc. For a 1-μg oxacillin disc we propose that 20 mm should be used as cut off for resistance, i.e. isolates with a zone diameter <20 mm are resistant to all β-lactam antibiotics except those with activity against methicillin-resistant staphylococci.